Penurunan Viabilitas Benih Padi (Oryza sativa L.) melalui Beberapa Metode Pengusangan Cepat - Simão Margono Belo (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2012)
Availability of seed lots with different viabilities is very important as the material for invigoration studies. Acceleratedor rapid aging methods is expected to serve seeds with different viabilities for those studies. The objective of this study was toobtain efficient seeds rapid aging method of rice seeds. The study consisted of three experiments i.e. rapid aging with ethanolgas, soaking seed in liquid ethanol (96%) and exposing seeds to 41 oC temperature and ± 100% relative humidity. Eachexperiment was arranged in a randomized block design with single factor that was length of aging with three replications.There were eight rice varieties used in this study, i. e. three varieties of upland rice, two verieties of lowland rice, and threevarieties of swamp rice. The results showed that the physical aging method could not produce reliable data due to fungusinfection on the treated seed. It was found that generally 60% and 50% viabilities of rice seed could be obtain by ethanol gastreatment for 4.9 and 5.3 hours, as well as by liquid ethanol for 4.0 and 4.4 minutes, respectively. Rapid aging method withliquid ethanol was the fastest and simplest method for decreasing seed viability of rice.Keywords: Ethanol, rapid aging, invigoration, seed viability